Multicriteria Strategic Environmental Assessment: a multimetodological approach - Ramos, Isabel Joaquina (2015)
The aim is to discuss and propose a Decision Aid Methodology for Strategic Environmental Assessment, seen as a promoter of the integration of sustainability issues on local land use plans. Due to the complexity of this decision-making process and the diversity of questions that emerge (particularly the difficulties in the design of intervention strategies taking into account the different areas of concern and the values of the different actors involved), it appears not to be possible to find all the answers in the framework of a single methodology. A combination of methodologies is recommended, coming into the trans- disciplinary conceptual field of “Multimethodologies”. The proposal is the combination of the Strategic Environmental Assessment Methodology with the Multicriteria Decision Aid Methodology, and to develop a Multicriteria Strategic Environmental Assessment Methodology.